Analisis Reaksi Pasar Modal Pada Peristiwa Politik Pemilihan Umum Di Indonesia, Malaysia, dan Thailand: Keywords: General Election; Abnormal Return; Trading Volume Activity - Sri Arum Endang Setyowati; Hariyati Hariyati (Universitas Negeri Surabaya, 2022)
This research has purpose to determine the existence of market reactions by analyzing differences of abnormal return and trading volume activity in the general election events held by Indonesia, Malaysia and Thailand. The approach used is event study with 5 days before and 5 days after the event. The population and research sample are the LQ45 Index, FBMKLCI and SET50. The samples that used was 125 companies. The statistical method used is One Sample t-Test also Paired Sample t-Test with the help of SPSS. The results prove that there are no reaction around the Indonesia, Malaysia and Thailand election. This research also showed there is no significant differences in the abnormal return and trading volume activity in the general election events in Indonesia, Malaysia and Thailand.Keywords: General Election; Abnormal Return; Trading Volume Activity